PENGEMBANGAN MEDIA PEMBELAJARAN PostDo (POSTER DAN EDMODO) PADA MATERI EKSKRESI MANUSIA - Prasmala, Erfitra Rezqi; Agustin, Khusnia; Irmawati, Farizha (Inteligensi : Jurnal Ilmu Pendidikan, 2023)
This study aims to find out how the development of PostDo as a learning medium on human excretory system material. This research was a development-research with a 4D development model consisting of 4 main stages, namely: Define, Design, Develop, Disseminate which will later produce PostDo learning media with a combination of Poster and Edmodo. Based on the validation results of validators of PostDo media obtained a score of 4.4 with "good" criteria for media validators, a score of 4.35 with "good" criteria, and 4.3 with "good" criteria for practitioner validators. Research results, it can be concluded that PostDo learning media on excretory system material was good and suitable for use in Biology learning, because visually it has a combination of colors that attract students' attention, and was be able to understand students of the material taught so as not to make students bored quickly and is able to train students' critical thinking power in understanding and translating the content of the material in the poster.